Water Management Strategies on Campus: An integrated approach - Pomin Li; Herlin Chien; Pearl Chang; Shanghua Chou; Chang-Hsien Tai (Journal of Sustainability Perspectives, 2022)
Water resource management strategies at National Pingtung University of Science and Technology (NPUST) are orientated towards water conservation, efficient water use and wastewater reuse. Ground water is the main water source on the university campus and the affiliated Tajen and Baoli experimental forest farms. To promote ground water collection from surface runoff water, permeable pavement, and multiple ponds have been installed. To achieve efficient water use, less efficient appliances have incrementally been replaced by more water-efficient ones. This has proven to be a feasible and effective way to achieve goals without bringing about inconveniences to campus users. Drought-tolerant trees have been planted and drip irrigation systems utilized on campus farms to save water. Our water reuse strategies aim to achieve a fully-recycling, zero emission water treatment system. Treated domestic sewage, swimming pool water and harvested rainwater are reused for flushing toilets or watering plants. Many facilities on campus, such as the Laifu Garden, Jingsi Lake, Green Park, Yingxia Lake, and Tajen Forest Farm, are more than just beautiful scenic spots; they all play major parts in the circular water ecosystem.Keyword: Water management, water conservation, water recycling, wastewater treatment